Ethnomedicinal survey of plants used by the folk medicinal practitioner (FMP) in the Jamalpur sadar Upazila, Jamalpur district, Bangladesh (Asian Journal of Medical and Biological Research, 2018)
The Folk medicinal practitioner (FMP) or Kabiraj plays a key role to provide health support mainly to village people. They are mainly dependent on the pants parts available around them and many modern medicines are being synthesized by extracting the active chemicals from plants. The main objective of this study is to document the plants used by the FMPs of two villages of Jamalpur sadar upazila. For this study, we conducted a survey based on semi structured method. We found they use mainly 31 plants belonging to 25 families. The part mostly used is leave (31.75%) and the least used is the flower (6.34%). It is found that almost 18 types of diseases are being cured by their formulation. This study also suggested that, the FMPs treat many common disorder like gastro intestinal disorder, Respiratory tract infection, diabetes, Skin disorder etc. and also various complicated disorder such as debility, anemia, neural disorder etc. This study may be helpful to create scientific view about the plants used by the FMPs of Jamalpur sadar upazila and these plants might be used to synthesize drug molecule of interest.Asian J. Med. Biol. Res. December 2018, 4(4): 422-426